Essa dissertação é divertida: predicados de gosto pessoal e seus aspectos sintáticos, semânticos e pragmáticos - Marques, Marina Nishimoto (Universidade Federal de São Carlos, 2018)
Predicates of personal taste (PPTs) are, as suggested by their name, predicates that speak of the personal taste of the speakers who utter them. They are diferent from the other predicates because they generate between the spekers disagreements in which, although one directly denies what the other says, no one is uttering something false – a phenomenom that has been called faultless disagreement in the literature (Lasersohn, 2005). In this work, we investigate some of the syntactic, semantic, and pragmatic aspects of predicates of personal taste, approaching the main problems that these items generate (the faultless disagreement being one of them, but not the only one), and how the literature about the theme deals with these problems and proposes a treatment for PPTs. We focus on three approaches: the relativist (Lasersohn, 2005; Stephenson, 2007), the contextualist (Pearson, 2013), and the expressivist (Gutzmann, 2016). Furthermore, we show how dta from Brazilian Portuguese contributes to the study of these constructions, casting a light on problems that are not approached in the English-directed theories, like, for example, the classification of these predicates in individual or stage level, and also how syntactic aspects of the language contribute to the generation of different inferences related to PPTs. Finally, we also show other items that behave in a similar manner to taste predicates and that could also be treated by a theory that is capable of explaning PPTs and their problems.
This dissertation is fun: predicates of personal taste and their syntactic, semantic, and pragmatic aspects
Keywords: Semântica; Predicados de gosto pessoal; Modalidade; Semantics; Modality; Predicates of personal taste; Faultless disagreement; LINGUISTICA, LETRAS E ARTES::LINGUISTICA